A Matter of Life and Death? Hospital Distance and Quality of Care - Evidence from Emergency Hospital Closures and Myocardial Infarctions - Daniel Avdic (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
The article analyzes to which extent residential proximity from an emergency hospital affects the probability of surviving an acute myocardial infarction (AMI). The critical time aspect in AMI treatment provides an ideal application for evaluating this proximity outcome hypothesis. Previous studies have encountered empirical difficulties relating to potential endogenous health-based spatial sorting of involved agents and data limitations on out-of-hospital mortality. Using policyinduced variation in hospital distance arising from plausibly exogenous emergency hospital closures in the highly regulated Swedish health care sector, and data on all AMI deaths in Sweden over two decades, estimation results show a clear, robust and gradually declining probability of surviving an AMI of about two percentage points (three percent) per additional ten kilometers distance from a hospital. Results further show that spatial sorting and sample selection from outof-hospital mortality are likely to significantly attenuate the distance effect unless accounted for.
Keywords: C23; I14; I18; R41; 330; myocardial infarction; geographical access; hospital closures; health policy; spatial sorting; self-selection; out-of-hospital mortality; causal effect